Peran guru IPS dalam mendorong etika kedisiplinan siswa di SMP NU Bululawang - Aditya, Rizky (Maliki Interdisciplinary Journal, 2024)
The study of student discipline in the educational environment is very important to study in more depth. In the educational context at NU Bululawang Middle School, the role of social studies teachers in encouraging students’ disciplinary ethics is very important. This is because these studies never stop being debated. The aim of this article is to understand 3 things: First, the paradigm of the role of social studies teachers in encouraging student disciplinary ethics at NU Bululawang Middle School. Second, internal and external factors that influence this role. Third, the positive and negative implications of the role of social studies teachers in encouraging students’ disciplinary ethics at NU Bululawang Middle School on learning activities. The methods used in this research were direct observation in the school environment, interviews with teachers, and analysis of documents related to school discipline policies. The approach used is a qualitative approach based on theories about character formation and student discipline.